PENGARUH PENDEKATAN OPEN-ENDED DAN PENDEKATAN SCIENTIFIC TERHADAP KEMAMPUAN KONEKSI MATEMATIK SISWA SEKOLAH DASAR - Fadhilaturrahmi, Fadhilaturrahmi (Mimbar Sekolah Dasar, 2017)
This study aims to see the influence of open-ended and scientific approach to improving mathematical connection ability of elementary school students. This study is a quasi experimental research, with the design used is "pretest-posttest two treatman design". The population as well as the sample in this research is all the students of grade v of elementary school in SDN 016 Bangkinang Kota. The instrument used in data collection is a mathematical connection test of the description form. The result of the research shows that the learning of mathematics both open-ended and scientific approach have the same effect in improving mathematic connection ability of elementary school students. If reviewed under the category of student ability, high group connection capabilities with a scientific approach are as good as high-group connection capabilities in an open-ended approach. The ability of a moderate group connection with a scientific approach is better than group connection capability is in an open-ended approach. Also in low-group connection capabilities with a scientific approach as well as a low-group connection capability in an open-ended approach. Based on the results of this study, then the learning of mathematics with scientific and open-ended approach can be used as one of the learning that can be applied in an effort to improve the ability of students, especially the ability of mathematical connections of elementary school students.Keywords: open-ended, scientific, mathematical connection ability, elementary students.